If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 1(13) + 2 Multiply 1 * 13 Y = 13 + 2 Combine like terms: 13 + 2 = 15 Y = 15 Solving Y = 15 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 15
| 67=9x+4 | | x-11=9+3x | | 3x+5=-8(6+5x) | | (X+3)(X+3)=16-2X^2 | | 7x+4y=109.50 | | 48d=32 | | -2-2y+10=0 | | .2x+4=.4x+10 | | 80=38.21+0.50x | | 17+x=10+12 | | 175(431-y)+200y=80625 | | 68-(7x+3)=7(x+5)+x | | mz^2-4mz-32m=0 | | (2-3)=m(4-5) | | 3+10=1 | | 6*1.5*n=9.75 | | 6(4)+4= | | Y=(13)+2 | | 8x+12+2x-9=6x-5 | | -7-5=a | | x^2-13=x-49 | | 4=[9-3(5w+1)]-5w | | 2x+9=23-5x | | 5(3(4)+8)= | | 95=-19a | | 2cos(4x)-(sqrt(3))=0 | | 3(a+1)-5=3a-w | | 4(k+4)=-2(2k-5)-18 | | 5x^2+-10x+-625=-604 | | 5k-3+9+k=180 | | 6u+2-4u-2(-2u-1)=2(u-3) | | 8(v-7)=8 |